Energetic activity for depression in young people aged 13–17 years: the READY feasibility RCT - Smith, Megan; James, Ryan; Howlett, Neil; Mengoni, Silvana; Jones, Julia; Sims, Erika; Turner, David; Grant, Kelly; Clark, Allan; Murdoch, Jamie; Bottoms, Lindsay; Wilson, Jonathan; et al. (Health technology assessment (Winchester, England), 2024)
Prevalence of depression is increasing in young people. Behaviour change interventions providing benefits equal to or greater than talking therapies or pharmacological alternatives are needed. Exercise could be beneficial for young people with depression, but we lack robust trials of its effectiveness. To test whether an exercise intervention targeting young people with depression is feasible, including recruitment and retention of young people, recruitment and training of exercise professionals and intervention delivery. Three-arm cluster feasibility randomised controlled trial with embedded process evaluation and health economic data collection. Local community venues in Hertfordshire, Bedfordshire and Norfolk. Young people aged 13-17 years experiencing mild to moderate low mood or depression (indicated by scoring 17-36 on the Child Depression Inventory version 2) identified by mental health services, schools or self-referral. Participants were randomised to one of three groups: high-intensity exercise, low-intensity exercise or a social activity control. Group sessions ran twice-weekly for 12 weeks delivered by registered exercise professionals, supported by mental health support workers. Referral, recruitment and retention rates; attendance at group sessions; adherence to and ability to reach intensity during exercise sessions; proportions of missing data, and adverse events measured at baseline and at 3 and 6 months; resource use; and reach and representativeness. Of 321 referrals to the study, 173 were assessed for eligibility, and of the target sample size of 81, 15 were recruited and 14 were randomised (one withdrew). The retention rate was 71.4% and attendance at intervention sessions was > 67%; data completeness was > 80% for baseline assessments. Follow-up completion rate at 14 weeks was > 80% for most outcomes, with 50% for accelerometer data in the low-intensity group. Trial processes and the intervention were acceptable to young people. Barriers to and facilitators of intervention delivery were identified. Findings highlighted challenges around recruitment, delivery of exercise interventions and informed ways of addressing barriers to recruitment for future studies. The study was conducted between October 2020 and August 2022 and consequently the COVID-19 pandemic had a disruptive impact on implementation. A large randomised trial of the effectiveness of the intervention is not feasible using the current study design, but issues relating to recruitment could be addressed with further work. Developing appropriate recruitment strategies via triage services, general practitioner practices, schools and social media and early engagement with the local Clinical Research Network to support recruitment to the study would address the significant shortfalls identified. Young people who are deemed unsuitable for mental health services should be followed up to be offered participation in such interventions. Collaborations between the NHS services and sports delivery partners should consider in-person contact with young people rather than remote consultations. Recruiting through general practitioner practices is effective and relatively inexpensive. The role of community engagement (socialmedia, public health agencies, community groups) needs to be further explored. Strong public and patient involvement and engagement via young people advisory groups is important to ensure that research is relevant to young people. This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number 17/78/10.